2007
DOI: 10.1021/ic061753a
|View full text |Cite
|
Sign up to set email alerts
|

DNA Binding Studies of Novel Copper(II) Complexes Containing l-Tryptophan as Chiral Auxiliary:  In Vitro Antitumor Activity of Cu−Sn2 Complex in Human Neuroblastoma Cells

Abstract: Novel trinuclear complexes C23H31N6O6CuSn2Cl5 [1], C23H31N6O6CuZr2Cl5 [2], C23H31N6O6ZnSn2Cl5 [3], and C23H31N6O6ZnZr2Cl5 [4] were synthesized and characterized by spectroscopic (IR, 1H, 13C, 2D COSY, and 119Sn NMR, EPR, UV-vis, ESI-MS) and analytical methods. In complexes 1-4, the geometry of copper and zinc metal ions were described as square-based pyramidal with l-tryptophan coordinated to copper/zinc via carboxylate group while Sn/Zr was present in the hexacoordinate environment. The interaction of 1 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
111
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(118 citation statements)
references
References 71 publications
7
111
0
Order By: Relevance
“…The primary amine exhibits a band at higher frequency than that of the corresponding secondary amine. In case of Journal of Chemistry 5 mononuclear complex, a broad and strong band is observed for ](N-H) in the range of 3218-3255 cm −1 which swings over to lower frequency region in case of bimetallic complexes [8] evidently specifying the formation of bond between group 14 metal and nitrogen, while bands due to (N-H) appear in the region of 1529-1540 cm −1 with no evident change after chelation [9]. Aromatic ring (C=C) stretching appears at 1645, 1529, and 1453 cm The far IR spectra show a distinct band at 315 cm −1 attributed to (Cu-Cl) band [11].…”
Section: Infrared Spectramentioning
confidence: 99%
“…The primary amine exhibits a band at higher frequency than that of the corresponding secondary amine. In case of Journal of Chemistry 5 mononuclear complex, a broad and strong band is observed for ](N-H) in the range of 3218-3255 cm −1 which swings over to lower frequency region in case of bimetallic complexes [8] evidently specifying the formation of bond between group 14 metal and nitrogen, while bands due to (N-H) appear in the region of 1529-1540 cm −1 with no evident change after chelation [9]. Aromatic ring (C=C) stretching appears at 1645, 1529, and 1453 cm The far IR spectra show a distinct band at 315 cm −1 attributed to (Cu-Cl) band [11].…”
Section: Infrared Spectramentioning
confidence: 99%
“…Hydrodynamic measurements that are sensitive to changes in DNA length are regarded as the least ambiguous and most critical tests of a binding model in solution in the absence of crystallographic data [25,26]. In classical intercalation, the DNA helix lengthens as base pairs are separated to accommodate the bound complex, leading to increased DNA viscosity, whereas a partial, non-classical complex intercalation causes a bend (or kink) of the DNA helix and reduces its effective length and thereby its viscosity [27].…”
Section: Viscosity Measurementsmentioning
confidence: 99%
“…It has been found that intercalation or electrostatic interaction between the metal complex and DNA leads to hypochromism, whereas hyperchromism indicates the breakdown of the secondary structure of DNA [41]. The absorption titrations have been employed to ascertain the DNA binding strength of complexes by monitoring the changes in the absorption intensity of the ligand-centered bands around 317-322 nm.…”
Section: Binding Characteristics Of Complex With Dnamentioning
confidence: 99%